Unterwegs mit Maus Molli - Schwendimann, Maria; Bühler, Martina; Greber, Larissa; Lehnherr, Heidi; Trepp-Bühlmann, Seraina (Schwendimann, Maria Deutsch Eins., 2022)
Heft 2 deckt den Unterricht von Januar bis Juni ab.